Promising Current Trends of Plant Biotechnology and Prospective Future for Sustainable Development of Medicinal Plants and Their Applications in Phytotherapy (Plant Tissue Culture and Biotechnology, 2025)
Plant cell tissue and organ culture (PCTOC) technology is one of the most significant biotechnology branches, called plant biotechnology. It is applied in production and conservation of medicinal plants for phytotherapy, to combat communicable and non-communicable diseases. Plant biotechnology is a proven technique for quick propagation of medicinal plants, particular endangered species. Medicinal plants are the most valuable source of human life saving drugs that play an essential role in health issues mitigation all over the world's population. This current work intends to highlight the outlines of PCTOC biotechnology for enhancement of valuable bioactive metabolites accumulation in plant tissue yields of medicinal plants via elicitation processes using various biotic and abiotic elicitors. This design will deliver mass production of valuable metabolites aggregations, to be used on scale up production for pharmaceutical preparations. Not only that but also, this work elucidates much interest of green and nano-green biotechnology as recent advances in plant biotechnology applications in our life. This study aimed to epitomize the key investigations and advance made in studying plant biotechnology trends, for medicinal plants development and prospective phytotherapy. Plant biotechnology products can be marketed commercially as natural therapeutic medicines and food supplementary.Plant Tissue Cult. & Biotech. 34(2): 255-289, 2024 (December)